2018
DOI: 10.1111/add.14417
|View full text |Cite
|
Sign up to set email alerts
|

Gendered violence and overdose prevention sites: a rapid ethnographic study during an overdose epidemic in Vancouver, Canada

Abstract: Although women who use drugs in Vancouver, Canada appear to feel that overdose prevention sites address forms of everyday violence made worse by the overdose epidemic, these sites remain 'masculine spaces' that can jeopardize women's access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
98
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(107 citation statements)
references
References 66 publications
(98 reference statements)
5
98
3
1
Order By: Relevance
“…There is also increasing evidence of the feasibility, acceptability and positive health impacts of peer-run SCFs (Bergamo et al, 2018;Boyd et al, 2018;Kerr et al, 2005;Kerr et al, 2003;McNeil et al, 2015;. For example, in a previous feasibility study, some subpopulations of PWUD in Vancouver indicated a strong preference for peer-run SCF models over facilities operated by health professionals (Kerr et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also increasing evidence of the feasibility, acceptability and positive health impacts of peer-run SCFs (Bergamo et al, 2018;Boyd et al, 2018;Kerr et al, 2005;Kerr et al, 2003;McNeil et al, 2015;. For example, in a previous feasibility study, some subpopulations of PWUD in Vancouver indicated a strong preference for peer-run SCF models over facilities operated by health professionals (Kerr et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In response, various harm reduction strategies have been implemented or expanded in BC, particularly in Vancouver's Downtown Eastside, a neighbourhood with a large open drug scene and high levels of poverty and homelessness, but also a history of drug user-led activism (BC Ministry of Health and Addictions, 2018;Boyd et al, 2009;Kerr et al, 2017). Much of the response to the overdose epidemic in this neighbourhood has been spearheaded by peers involved in collective action initiatives and harm reduction programming delivered as part of the public health system and established peer-based drug user organizations in the Downtown Eastside (Bardwell et al, 2018b;BC Ministry of Health and Addictions, 2018;Boyd et al, 2018;Jozaghi et al, 2018;Kerr et al, 2017). For example, peers have led the development and implementation of interventions such as naloxone training, distribution and response initiatives, as well as unsanctioned SCFs, including "pop-up" SCF tents that were erected in the Downtown Eastside beginning in September 2016 (Boyd et al, 2018;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transient relationships are reported and many of them engage in unprotected sex [8] and some type of violence [9]. WWID in the US face high levels of stigma, punishing drug laws, increasing rates of drugrelated incarceration and restricted access to harm reduction services, specifically gender-sensitive services [10]. In Canada, the increase in overdoses in British Columbia has increased violence against WWID, particularly among poor, homeless, transgender and indigenous women.…”
Section: Introductionmentioning
confidence: 99%
“…These studies suggest that fentanyl is being used to adulterate other drugs; however, they do not focus specifically on women or people who use stimulants. Impoverished women who use drugs face vulnerability to drug-related harms differently than do men, due to factors such as gendered violence and gendered norms regarding drug use, sex, and reproductive health [15][16][17].…”
Section: Introductionmentioning
confidence: 99%